2019
DOI: 10.3892/mmr.2019.10080
|View full text |Cite
|
Sign up to set email alerts
|

High expression of B7‑H2 or B7‑H3 is associated with poor prognosis in hepatocellular carcinoma

Abstract: B7 family members have been associated with the signaling transduction pathways underlying tumor immune evasion in hepatocellular carcinoma. In the present study, associations between the clinical characteristics of patients with hepatocellular carcinoma (HCC) and the expression of B7-H2 and B7-H3 were analyzed. A total of 63 formalin-fixed and paraffin-embedded HCC tissues were collected to be used as a tissue microarray. Following this, the association between B7-H2/B7-H3 and the prognosis of patients with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…The four immune subtypes were validated by IHC in 72 HCC patients from South China. The results have shown the following: (i) there is an association between high B7-H3 expression and poor survival in HCC, which is consistent with previous reports [21][22][23][24]; (ii) B7-H3 expression is positively associated with CD8 expression and a Th1/IFNγ gene signature in HCC; and (iii) patients with B7-H3 low /CD8 high subtype are correlated with favorable survival in HCCs. Our findings support the view that, despite the limited efficiency of immunotherapy, the endogenous antitumor immune response is a critical factor for survival Figure 6.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The four immune subtypes were validated by IHC in 72 HCC patients from South China. The results have shown the following: (i) there is an association between high B7-H3 expression and poor survival in HCC, which is consistent with previous reports [21][22][23][24]; (ii) B7-H3 expression is positively associated with CD8 expression and a Th1/IFNγ gene signature in HCC; and (iii) patients with B7-H3 low /CD8 high subtype are correlated with favorable survival in HCCs. Our findings support the view that, despite the limited efficiency of immunotherapy, the endogenous antitumor immune response is a critical factor for survival Figure 6.…”
Section: Discussionsupporting
confidence: 90%
“…To elucidate the clinical significance of the upregulated immune checkpoints, we analyzed the relationship between these genes and overall survival (OS) of HCC patients. The results show that only two genes are significantly associated with poor OS: CD276 (B7-H3) (P = 0.014, Figure 2A) and CD47 (P = 0.039, Figure 2B), consistent with previous reports [20][21][22][23][24][25]. All the others do not have a statistically significant relationship with survival ( Supplementary Figure 1).…”
Section: The Expression Patterns and Clinical Significance Of Immunomsupporting
confidence: 89%
See 1 more Smart Citation
“…B7-H3 is mostly upregulated in several cancer types, including liver, breast, bladder, colorectal, cervical, glioma, esophageal and gastric cancer (53). Previous studies have also demonstrated that dysregulation of B7-H3 in Hcc results in impaired T-lymphocyte function, thus leading to poor prognosis and recurrence (54,55). in muscle-invasive bladder cancer, high expression of B7-H3 was associated with a poor clinicopathological status and poor prognosis (56).…”
Section: Discussionmentioning
confidence: 99%
“…inducible T cell costimulator ligand; ICOSL) and B7-H3 are being explored as novel immunotherapeutic targets in other cancer types (119). In HCC, both independent or combined expression of B7-H2 and B7-H3 have correlated to recurrence and poorer survival rate of the patients (120). Although further understanding of the tumor-promoting mechanisms by B7 ligands in the context of HCC is required, they could become promising combinatorial agents in treating HCC in the future.…”
Section: Major Concerns Of Intervention(s)mentioning
confidence: 99%